Neutrinos and implications for physics beyond the standard model - editor; R. Shrock
This important book presents the proceedings of the conference "Neutrinos and Implications for Physics Beyond the Standard Model", put on by the Yang Institute for Theoretical Physics, State University of New York at Stony Brook. The observation of neutrino masses and lepton mixing constitutes the first confirmed evidence for physics beyond the Standard Model. This evidence includes the measured deficiency.